1993
DOI: 10.1108/01425459310038889
|View full text |Cite
|
Sign up to set email alerts
|

Line Managers, Human Resource Specialists and Technical Change

Abstract: Draws on findings from recent survey and case study evidence to identify key aspects of the relation between technical change and human resource management. Begins by examining the primary role played by general and line managers in managing advanced technical change. Also highlights the persistent and widespread support for technical change among both manual and non‐manual workers. Analyses three examples where human resource specialists have played a proactive role in the introduction of technical change, id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 1 publication
0
14
0
Order By: Relevance
“…This act of `giving personnel away', or perhaps ultimately embracing the possibility of `personnel management without personnel managers', may in fact be a measure of the `mature future ' of a role that is ® nally con® dent of its contribution to business success (Paauwe, 1995; Ty s o n and Wi t c h e r, 1994). Change agent roles certainly offer the prospect of a way out of the traditional debate on marginalisation versus the overblown ambitions of a pro f e s s i o n constantly seeking to secure its professional status and legitimacy (Legge, 1993;Clark, 1993).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This act of `giving personnel away', or perhaps ultimately embracing the possibility of `personnel management without personnel managers', may in fact be a measure of the `mature future ' of a role that is ® nally con® dent of its contribution to business success (Paauwe, 1995; Ty s o n and Wi t c h e r, 1994). Change agent roles certainly offer the prospect of a way out of the traditional debate on marginalisation versus the overblown ambitions of a pro f e s s i o n constantly seeking to secure its professional status and legitimacy (Legge, 1993;Clark, 1993).…”
Section: Resultsmentioning
confidence: 99%
“…As one divisional HR director noted, having organised the corporate HR function as a `central service silo' of consultancy and advice it was inevitable that line managers would also see the advantages of a parallel silo of `added value external consultancy services' that could be bought in as needed (Purcell and Ahlstrand, 1994). Ultimately, this potential `externalisation' and diff e rentiation of HR services into discrete projects and parcels of expertise has an impact on the variety and scope of the roles the internal HR change consultant may perform (Adams, 1991;Clark, 1993;Tamkin et al, 1997;Ulrich, 1997).…”
Section: Change Consultantsmentioning
confidence: 99%
“…Many of these saw an attempted switch from the 'traditional supervisor', to the 'first line manager', who was expected to embody a new management style which included involving, developing and communicating with employees. It is also worth noting here that Clark (1993) has found that technical change has also led line managers to become more involved in employee relations issues.…”
Section: Role Of Line Managers Under Hrmmentioning
confidence: 95%
“…A number of authors have already produced handsome overviews of HRM aspects of innovations -although they do not label them as such, preferring terms such as 'organisational innovation' or 'organising for innovation'. Examples of these are Damanpour (1991), Clark (1993), Brown and Eisenhardt (1995), Tidd, Bessant and Pavitt (1997) and Dougherty (1996). Based on these overviews, and our own review of the literature (de Leede, Looise & de Weerd-Nederhof, 1999), we have drawn up the following list of topics concerning the role of aspects of HRM in connection with innovation:…”
Section: Innovation and Hrm: Is There A Basis For Integration?mentioning
confidence: 99%